DPPH free radical scavenging activity and total phenolic content of Talisay. - Bohol, Lyan Jean Basilio
Free radicals, a class of highly reactive molecules derived from the metabolism of oxygen is believed to be involved in many health disorders. It is generated as by-products of biological reactions or from environment. Antioxidant-based drugs and formulations for the prevemtion and treatment of complex diseases have attracted a great deal of research interest in natural antiosidants. It is deemed necessary to screen medicinal plants for their antioxidant potential. Terminalia catappa is a widely-distributed tree in the Philippines with promising potentials in pharmacology. Evaluation of the in vitro antioxidant activity of mnethanolic, dichloromethane, and hexane extracts of terminlaia catappa seeds were carried out using two essays: a, 1-diphenyl-2-pycrylhdrazyl (DPPH) free radical scavenging assay and total phenolic content assay. Results revealed that methanolic